2017
DOI: 10.25165/j.ijabe.20171006.2614
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sandy soil moisture content with hyperspectral imaging

Abstract: In this study, a rapid and non-invasive technology for predicting soil moisture content (SMC) was presented based on hyperspectral imaging (HSI). Firstly, a set of HSI system was developed to collect both spectral (400-1000 nm) and spatial (1620×841 pixels) information from sandy soil samples with variable SMC levels in the laboratory. Principal component analysis (PCA) transformation, K-means clustering, and several other image processing methods were performed to obtain a region of interest (ROI) of soil sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…By comparing the correlation between the spectral reflectance and SMC after treatment with different pretreatment methods, we found that the proper application of pretreatment methods can improve the correlation between the spectral reflectance and SMC, and at the same time, the sensitive band of SMC can be more obviously highlighted. This conclusion was confirmed in previous studies (Qi et al., 2017). For example, Jia et al.…”
Section: Discussionsupporting
confidence: 91%
“…By comparing the correlation between the spectral reflectance and SMC after treatment with different pretreatment methods, we found that the proper application of pretreatment methods can improve the correlation between the spectral reflectance and SMC, and at the same time, the sensitive band of SMC can be more obviously highlighted. This conclusion was confirmed in previous studies (Qi et al., 2017). For example, Jia et al.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the original data must be processed to extract the spectral data. The entire area of a single maize seed in the image is taken as the region of interest (ROI), and then the average reflectance of all pixels in the ROI is calculated as the spectral value of each maize seed ( Qi et al, 2017 ). Its value can be calculated using the following equation: m , which is the number of all pixels in the ROI area, and A ij is the spectral value of the i-th pixel in the j-th band.…”
Section: Methodsmentioning
confidence: 99%
“…Soil moisture (SM) is an important parameter in crop growth and produces a significant variation in soil spectral reflectance [11,12]. For wet soils, the difference between the refractive index of soil (nsoil, λ approximately 1.50) and water (nwater, λ approximately 1.33) is smaller than that of dry soils, where the particles are surrounded by air (nair, λ approximately 1.00).…”
Section: Introductionmentioning
confidence: 99%